APPLICATION PROBLEM BASED LEARNING MODEL IN IPAS LEARNING TO IMPROVE LEARNING OUTCOMES OF GRADE V OF SIMAJA STATE ELEMENTARY SCHOOL - Tanisa, Siti; Darmini, Mimin; Sati, Sati (Universitas Bhinneka PGRI, 2026)
This research is motivated by the low learning outcomes of V grade Students. This is evidenced by the results of observations and interviews conducted with V grade teachers that students are less actively involved, less interested, and have difficulty concentrating, so they have difficulty in finding, analilyzing, and concluding in IPAS learning. Of the 22 students, there are 9 student who get scores according to the KKTP (Criteria for Achieving Learning Objectives) in learning.this is due the implementation of less innovative learning models, limited variety of methods, and minimal use of relevant media. This study to improve student learning outcomes throught the application of the Problem Based Learning (PBL) model. This study uses the Classroom Action Reasearch (CAR) Method. The research design in this study, namely the Kemmis and Tanggart model, consists of four steps, namely planning, implementation, observation, and reflection. The results of study showed that there was an increase in student learning outcomes in Cycle I of 68,18% and Cycle II of 86,36% after the implementation of the Problem Based Learning (PBL) model. Therefore, it can be concluded that the PBL model can improve the learning outcomes of V grade students in IPAS Lessons